Full-dimensional super-amphiphobic concrete as well as preparation method and application thereof

By introducing modified ultra-double fine sand and hydrophobic cement powder into the concrete, the full-dimensional ultra-double sparse concrete is solved, and the problems of poor durability of ordinary concrete in high-salt and high-humidity environments and easy pollution of facade decoration are achieved, and excellent water resistance and oil resistance and extended service life are achieved.

CN119661129APending Publication Date: 2025-03-21NANJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411798625.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Ordinary concrete has poor durability in high salt and high humidity environments, and the facade decorative concrete walls are prone to mold, ash, and stains.

Method used

The preparation method of full-dimensional ultra-double-spark concrete is adopted. By emulsifying fine sand in a cationic surfactant solution, and adding silica sol and hydrophobic modifier, a modified ultra-double-spark fine sand and hydrophobic cement powder are formed, and a surfactant and dispersant are combined to form a full-dimensional ultra-double-spark concrete slurry.

Benefits of technology

It significantly improves the water and oil resistance of concrete, extends its service life, and provides dual protection between the surface and the internal structure, enhancing durability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661129A_ABST
    Figure CN119661129A_ABST
Patent Text Reader

Abstract

The invention discloses full-dimensional super-amphiphobic concrete as well as a preparation method and application thereof. Ethanol, ammonia water, tetraethyl orthosilicate and fine sand are sequentially added into an aqueous solution of a cationic surface active agent and stirred, and a fine sand solution coated with silicon dioxide is obtained; adding silica sol into the fine sand solution coated with silicon dioxide, then adding a hydrophobic modifier while stirring, and then stirring to obtain modified super-amphiphobic fine sand; filtering, cleaning, drying and crushing the modified super-amphiphobic fine sand solution to obtain modified super-amphiphobic fine sand; the preparation method comprises the following steps: wetting cement powder by using an alkyl siloxane absolute ethyl alcohol solution, carrying out dry mixing treatment on the wetted powder in a mixing bottle added with agate balls, drying and crushing to obtain modified hydrophobic cement powder; and putting the modified super-amphiphobic fine sand and the modified hydrophobic cement powder into an aqueous solution containing a surfactant and a dispersant, and then stirring to form the full-dimensional super-amphiphobic concrete slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials and coating preparation thereof, and specifically relates to a full-dimensional super-amphiphobic concrete and a preparation method and application thereof. Background Art

[0002] Reinforced concrete structures are the most widely used building materials in the world due to their excellent properties such as easy pouring, impact resistance, and wear resistance. However, in special environments, such as coastal projects, saline soils, long-term use of deicing salts, or cold regions, the structural durability of reinforced concrete structures may be seriously deteriorated due to corrosion or freeze-thaw damage. Most buildings will suffer from severe corrosion damage after being used for more than a decade, which seriously affects the safe operation of the buildings. On the other hand, after long-term use, mold, dust, oily dirt, and microorganisms will appear on the walls of exterior wall facade decorative concrete materials, which will reduce the decorative effect of the facade and seriously affect the appearance and service life of the building.

[0003] The hydrophobic-self-cleaning effect produced on the surface of lotus leaves has attracted widespread attention and is called the "lotus effect". Since the discovery of the "lotus effect", after more than ten years of scientific research, it has shifted from theoretical experiments to application backgrounds, and has been widely used in the fields of self-cleaning, anti-corrosion and anti-mildew, anti-icing and anti-frost, and oil-water separation. The present invention applies super-hydrophobicity to construct full-dimensional super-amphiphobic concrete, and studies and prepares a full-dimensional super-amphiphobic concrete, which can effectively solve the problem of concrete durability and the problem of easy pollution of wall facade decoration surfaces. Summary of the invention

[0004] Technical problem to be solved: In order to solve the shortcomings of ordinary concrete, such as easy water seepage, poor durability in high-salt and high-humidity environments, and easy mold, dust and staining of facade decorative concrete walls, the present invention provides a full-dimensional super-amphiphobic concrete and its preparation method and application.

[0005] Technical solution: A method for preparing a full-dimensional super-amphiphobic concrete, comprising the following steps: successively adding ethanol, ammonia water, tetraethyl orthosilicate and fine sand to an aqueous solution of a cationic surfactant, and stirring to obtain a fine sand solution coated with silica; the mass ratio of each component is: 1-20 parts of a cationic surfactant, 50-150 parts of water, 100-300 parts of ethanol, 50-150 parts of ammonia water, 1-20 parts of tetraethyl orthosilicate, and 100-500 parts of fine sand; adding silica sol to the fine sand solution coated with silica, and then stirring to add a hydrophobic modifier, and then stirring to obtain modified super-amphiphobic fine sand; the mass ratio of each component is: 100-300 parts of a fine sand solution coated with silica, 1-50 parts of silica sol, and 1-20 parts of a hydrophobic modifier; filtering, washing, drying and crushing the modified super-amphiphobic fine sand solution to obtain 100 -200 mesh modified super-amphiphobic fine sand; the cement powder is wetted with an alkyl siloxane anhydrous ethanol solution, the wetted powder is dry-mixed in a mixing bottle with agate balls, and then dried and crushed to obtain a 300-500 mesh modified hydrophobic cement powder; the mass ratio of each component is: 100-500 parts of cement powder, 1-20 parts of alkyl siloxane, and 1-40 parts of anhydrous ethanol; 100-200 mesh modified super-amphiphobic fine sand and 300-500 mesh modified hydrophobic cement powder are put into an aqueous solution containing a surfactant and a dispersant, and then stirred to form a full-dimensional super-amphiphobic concrete slurry; the mass ratio of each component is: 50-200 parts of modified super-amphiphobic fine sand, 100-300 parts of modified hydrophobic cement powder, 0.8-1.8 parts of surfactant, 1.0-2.2 parts of dispersant, and 30-100 parts of water.

[0006] The fine sand is at least one of quartz sand screened through 200-400 meshes, treated building recycled sand, volcanic sand, natural river sand, limestone sand or a mixture of the above sands.

[0007] The cement powder is at least one of ordinary silicate cement, expansive cement, white silicate cement, high alumina cement, slag silicate cement, pozzolanic silicate cement and fly ash silicate cement.

[0008] The surfactant is at least one of nonylphenol polyoxyethylene ether (NP), alkyl polyglycoside (APG), polyether surfactant, stearic acid, fluorocarbon surfactant, and polyvinyl alcohol surfactant.

[0009] The hydrophobic modifier is alkylsiloxane, chlorosilane or fluorosilane.

[0010] The dispersant is at least one of sodium polyacrylate, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, trisodium phosphate, alkyl aryl sulfonate, polycarboxylic acid dispersant, polyethylene glycol or alkyl benzene sulfonate.

[0011] The full-dimensional super-amphiphobic concrete prepared by the above preparation method.

[0012] The above-mentioned full-dimensional super-amphiphobic concrete is applied in such a way that the full-dimensional super-amphiphobic concrete is evenly coated on the surface of the substrate by spraying, rolling or brushing, and after it is naturally dried at room temperature, a concrete coating with full-dimensional super-amphiphobic properties is formed; or, the full-dimensional super-amphiphobic concrete slurry is directly poured into a mold, and after it is naturally cured at room temperature, a concrete test block with full-dimensional super-amphiphobic properties is obtained.

[0013] Beneficial effects: (1) The cement fine sand particles are first emulsified in a cationic surfactant solution, which is not only conducive to the fine sand surface being attached with a large amount of positive charge, but also forms a preliminary stable interface layer on the fine sand surface through the self-assembly effect of the cationic surfactant, providing more adsorption sites for SiO2 generated by the subsequent hydrolysis of tetraethyl orthosilicate. This synergistic effect enables SiO2 to be deposited evenly and stably on the fine sand surface, further forming a rough porous structure, which is not only conducive to enhancing the super-amphiphobic properties of the modified fine sand, but also the process combines chemical adsorption with physical intercalation to improve the overall durability and stability of the coating. (2) By introducing modified super-amphiphobic fine sand and modified hydrophobic cement powder into concrete, the prepared concrete coating or test block exhibits excellent super-amphiphobic properties inside and outside the concrete matrix. The rough porous structure provided by the modified fine sand and cement powder works together with the nano-scale hydrophobic particles in the modified cement powder to significantly improve the overall water and oil resistance of the concrete, and ensure that the performance is evenly distributed throughout the structure, extending the service life. (3) Compared with ordinary concrete coatings or test blocks, the full-dimensional super-amphiphobic concrete coating or test block of the present invention exhibits dual protection capabilities of the surface and internal structure through the synergistic enhancement of modified fine sand and hydrophobic cement. Its surface has excellent super-amphiphobic properties, and the internal structure exhibits excellent anti-permeability and low water absorption. Even after multiple wear and tear, the super-amphiphobic performance is still maintained, thereby greatly improving its durability in extreme environments, especially in terms of anti-icing and acid-base corrosion resistance. (4) Compared with the existing super-amphiphobic technology, the inorganic coating system process adopted in the present invention is simple, does not require complex equipment or procedures, and has a production efficiency comparable to that of traditional concrete processes. It can be quickly applied to large-scale construction, significantly reducing construction difficulty and cost. (5) Compared with ordinary coating technology, the full-dimensional super-amphiphobic concrete coating or test block prepared by the present invention has excellent anti-fouling, dustproof and anti-corrosion properties, can maintain the beauty and stability of the building surface in various harsh climates and environments, and greatly improves the durability and service life of concrete exterior wall decoration materials. (6) The full-dimensional super-amphiphobic concrete prepared by the present invention has excellent protective properties while maintaining good air permeability, which helps to reduce the accumulation of water vapor inside the concrete and reduce the risk of structural aging or cracking caused by moisture, thereby improving the overall structural strength and durability of concrete buildings. (7) The full-dimensional super-amphiphobic concrete prepared by the present invention mainly uses inorganic materials and common chemicals, avoiding the use of organic solvents or other environmentally harmful substances in traditional coatings, meeting the requirements of modern buildings for environmental protection and sustainability, and reducing the impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 .Digital image of the morphology of water droplets and soybean oil on the surface of the full-dimensional super-amphiphobic concrete specimen (blue is water droplets, red is soybean oil).

[0015] Figure 2 .Scanning electron micrographs of the sand surface before and after modification.

[0016] Figure 3 .Digital image of water droplet morphology on the surface of full-dimensional super-amphiphobic concrete coating.

[0017] Figure 4 .The quality change of water drop contact angle on the surface of full-dimensional super-amphiphobic concrete coating with the number of sandpaper polishing. DETAILED DESCRIPTION

[0018] The present invention proposes a new method for preparing overall full-dimensional super-amphiphobic concrete, which effectively solves the technical problem of overall super-amphiphobic concrete. The method does not need to be equipped with an additional coating, has a simple process, is easy to operate, is suitable for large-scale preparation and production, and the obtained concrete has good overall super-amphiphobic property, and the interior is still super-amphiphobic after wear, and the super-amphiphobic property is not easily destroyed. The method is suitable for various concrete application sites and has a good prospect.

[0019] Example 1

[0020] Under the condition of low-speed mechanical stirring at 500rpm, 100 parts of ethanol, 100 parts of ammonia water, 2 parts of tetraethyl orthosilicate, and 150 parts of fine quartz sand were successively added to the cationic aqueous solution, and then stirred at a high speed of 2000rpm for 2h to obtain a fine quartz sand solution coated with silica; under the condition of low-speed mechanical stirring at 500rpm, silica sol was added to the fine quartz sand solution containing the silica sol coating layer, and fluorosilane hydrophobic modifier was added after 30min of high-speed stirring to obtain a modified super-double-dispersible fine quartz sand solution. The modified super-double-dispersible fine quartz sand solution was filtered, washed, dried and crushed to obtain 200-mesh modified super-double-dispersible fine quartz sand. 150 parts of cement powder were moistened with 5 parts of alkyl siloxane anhydrous ethanol solution, the moistened powder was poured into a mixing bottle, and after adding agate balls and dry mixing for 24h, the powder was dried and crushed to obtain 300-mesh modified hydrophobic cement powder. At a rotation speed of 500rpm, 150 parts of modified super-amphiphobic fine quartz sand and 150 parts of modified cement powder are added to an aqueous solution containing 0.8 parts of polyvinyl alcohol surfactant and 2 parts of polycarboxylic acid dispersant and stirred for 20 minutes to form a full-dimensional super-amphiphobic concrete slurry. The stirred slurry is poured into a culture dish, shaken and smoothed, and then naturally dried at room temperature to obtain a full-dimensional super-amphiphobic concrete specimen with a water drop contact angle of 159° and a rolling angle of 1°; an oil drop contact angle of 154° and a rolling angle of 4°. The digital image of the morphology of water droplets and oil droplets on the surface of the obtained full-dimensional super-amphiphobic concrete specimen is as follows Figure 1 As shown in the scanning electron microscope images of the sand surface before and after modification Figure 2 shown.

[0021] Example 2

[0022] Under the condition of low-speed mechanical stirring at 500rpm, 150 parts of ethanol, 150 parts of ammonia water, 6 parts of tetraethyl orthosilicate, and 200 parts of fine building regenerated sand were successively added to the cationic aqueous solution, and then stirred at a high speed of 2000rpm for 2h to obtain a fine sand solution coated with silica; under the condition of low-speed mechanical stirring at 500rpm, silica sol was added to the fine sand solution coated with silica, and chlorosilane hydrophobic modifier was added after high-speed stirring for 30min to obtain a modified super-double-repellent fine sand solution. The modified super-double-repellent fine sand solution was filtered, washed, dried and crushed to obtain 250 mesh modified super-double-repellent fine building regenerated sand. 200 parts of cement powder were moistened with 10 parts of alkyl siloxane anhydrous ethanol solution, the moistened powder was poured into a mixing bottle, agate balls were added and dry mixed for 24h, and then the powder was dried and crushed to obtain 250 mesh modified hydrophobic cement powder. At a rotation speed of 500 rpm, 250 parts of modified super-amphiphobic fine sand and 250 parts of modified cement powder were added to an aqueous solution containing 1.2 parts of fluorocarbon surfactant and 2.2 parts of sodium hexametaphosphate and stirred for 30 minutes to form a full-dimensional super-amphiphobic concrete slurry. The stirred slurry was sprayed onto the surface of an ordinary Portland cement block and naturally dried at room temperature to obtain a full-dimensional super-amphiphobic concrete coating with a water droplet contact angle of 152° and a rolling angle of 6°; an oil droplet contact angle of 150° and a rolling angle of 9°. The digital image of the water droplet morphology on the surface of the obtained full-dimensional super-amphiphobic concrete coating is shown below Figure 3 shown.

[0023] Example 3

[0024] Under the condition of low-speed mechanical stirring at 500rpm, 300 parts of ethanol, 180 parts of ammonia water, 15 parts of tetraethyl orthosilicate, and 180 parts of fine natural river sand were successively added to the cationic aqueous solution, and then stirred at a high speed of 2000rpm for 2h to obtain a fine sand solution coated with silica; under the condition of low-speed mechanical stirring at 500rpm, silica sol was added to the fine sand solution coated with silica, and a fluorosilane hydrophobic modifier was added after 30min of high-speed stirring to obtain a modified super-double-repellent fine sand solution. The modified super-double-repellent fine sand solution was filtered, washed, dried and crushed to obtain 400-mesh modified super-double-repellent fine sand. 360 parts of cement powder were moistened with 8 parts of alkyl siloxane anhydrous ethanol solution, the moistened powder was poured into a mixing bottle, and after adding agate balls and dry mixing for 24h, the powder was dried and crushed to obtain 180-mesh modified hydrophobic cement powder. At a speed of 500 rpm, 180 parts of modified super-amphiphobic fine sand and 160 parts of modified cement powder were added to an aqueous solution containing 1.4 parts of polyether surfactant and 1.2 parts of trisodium phosphate and stirred for 30 minutes to form a full-dimensional super-amphiphobic concrete slurry. The stirred slurry was brushed on the facade of the building, and dried naturally at room temperature to obtain a full-dimensional super-amphiphobic concrete coating with a water drop contact angle of 153° and a rolling angle of 6°; an oil drop contact angle of 150° and a rolling angle of 9°.

[0025] Example 4

[0026] The full-dimensional super-amphiphobic concrete coating prepared in Example 1 was taken out, and 100 g of fly ash was evenly sprinkled on the surface of the super-amphiphobic coating according to the national standard GB9780-2013 "Test method for stain resistance of architectural coatings". Then the sample was tilted 30° and the surface of the sample was impacted with deionized water at a certain speed. It was found that all the dust on the surface of the sample could be taken away without any residue on the surface, and the self-cleaning effect was excellent.

[0027] Example 5

[0028] Take out the full-dimensional super-amphiphobic concrete test block prepared in Example 1, place it under a 100g weight pressure, and rub it on 1200 mesh sandpaper. Each friction cycle refers to rubbing 10cm in the horizontal and vertical directions. Observe the change of its mass loss and surface water drop contact angle with the increase of the number of grinding times. After 10,000 grindings, its surface water drop contact angle is still 152°, and the water drop contact angle loss rate is as follows: Figure 4 shown.

[0029] Example 6

[0030] In order to verify the water absorption performance of the full-dimensional super-amphiphobic concrete test block, several full-dimensional super-amphiphobic concrete test blocks obtained in Example 1 were taken out, and ordinary Portland cement blocks with the same proportion were prepared for water absorption comparison test. According to the standard ASTMC1585-2013 "Standard Test Method for Measurement of Rate of Absorption of Water by Hydraulic-Cement Concretes", the test block was first placed in a sealed container, and the ambient temperature was maintained at 50±2° and humidity at 40±3°. After three days, the sample was transferred to another sealed container and maintained at an ambient temperature of 20±2° and a humidity of 40±3° for another 7 days. Then, a water absorption test was performed. The results show that for ordinary concrete, the water absorption rate after 9 days is as high as 0.25 mm 3 / mm 2 For the super-hydrophobic concrete specimen, the water absorption rate after 9 days was only 0.04 mm 3 / mm 2 , showing excellent resistance to water absorption.

[0031] Example 7

[0032] In order to verify the air permeability of the super-amphiphobic test blocks, several full-dimensional super-amphiphobic concrete test blocks obtained in Example 1 were taken out, and ordinary Portland cement blocks with the same proportion were prepared for air permeability comparison test. After the samples were cured for 90 days, φ25×30mm 2The part was placed on the automatic porosimeter, and nitrogen was used as the model. During the test, the gas pressure was maintained at 120-250psi and the confining pressure was maintained at 400-9000psi. The results showed that the gas permeability coefficient of ordinary concrete concrete block was about 1.1×10 -3 μm 2 , while the gas permeability coefficient of the full-dimensional super-amphiphobic concrete specimen is only 0.18×10 -3 μm 2 , its gas permeability is significantly reduced.

[0033] Example 8

[0034] In order to verify the chemical erosion resistance of the full-dimensional super-amphiphobic concrete coating, several full-dimensional super-amphiphobic concrete coatings obtained in Example 2 were taken out. The artificial corrosion solutions are: 5% hydrochloric acid solution, 5% NaOH solution and 5% MgSO4 solution. After the full-dimensional super-amphiphobic concrete coating is standardly cured for 28 days, it is placed in different erosion solutions for a certain age, and the surface contact angles of water droplets and oil droplets of the concrete coating are tested, and it is used as an indicator for evaluating the chemical erosion resistance of the full-dimensional super-amphiphobic concrete test block. The results show that after immersion in hydrochloric acid solution, NaOH solution and MgSO4 solution for 3 days, the surface water drop contact angles are 156°, 148° and 150° respectively, and the oil drop contact angles are 150°, 140°, 147° respectively, and the chemical erosion resistance is excellent.

Claims

1. A method for preparing a full-dimensional super-amphiphobic concrete, characterized in that: The following steps are involved: (1) Add ethanol, ammonia water, tetraethyl orthosilicate and fine sand to an aqueous solution of a cationic surfactant, and stir to obtain a fine sand solution coated with silica; the mass ratio of each component is: 1-20 parts of cationic surfactant, 50-150 parts of water, 100-300 parts of ethanol, 50-150 parts of ammonia water, 1-20 parts of tetraethyl orthosilicate, and 100-500 parts of fine sand; (2) Add silica sol to the fine sand solution coated with silica, and then stir to add a hydrophobic modifier, and then stir to obtain modified super-amphiphobic fine sand; the mass ratio of each component is: 100-300 parts of fine sand solution coated with silica, 1-50 parts of silica sol, and 1-20 parts of hydrophobic modifier; (3) Filter, wash, dry and crush the modified super-amphiphobic fine sand solution to obtain 100-200 mesh modified super-amphiphobic fine sand; (4) The cement powder is wetted with an alkyl siloxane anhydrous ethanol solution, and the wetted powder is dry-mixed in a mixing bottle with agate balls, and then dried and crushed to obtain a 300-500 mesh modified hydrophobic cement powder; the mass ratio of each component is: 100-500 parts of cement powder, 1-20 parts of alkyl siloxane, and 1-40 parts of anhydrous ethanol; (5) 100-200 mesh modified super amphiphobic fine sand and 300-500 mesh modified hydrophobic cement powder are added to an aqueous solution containing a surfactant and a dispersant, and then stirred to form a full-dimensional super amphiphobic concrete slurry; the mass ratio of each component is: 50-200 parts of modified super amphiphobic fine sand, 100-300 parts of modified hydrophobic cement powder, 0.8-1.8 parts of surfactant, 1.0-2.2 parts of dispersant, and 30-100 parts of water.

2. The method for preparing the full-dimensional super-amphiphobic concrete according to claim 1, characterized in that: The fine sand is at least one of quartz sand screened through 200-400 meshes, treated building recycled sand, volcanic sand, natural river sand, limestone sand or a mixture of the above sands.

3. The method for preparing the full-dimensional super-amphiphobic concrete according to claim 1, characterized in that: The cement powder is at least one of ordinary silicate cement, expansive cement, white silicate cement, high alumina cement, slag silicate cement, pozzolanic silicate cement and fly ash silicate cement.

4. The method for preparing the full-dimensional super-amphiphobic concrete according to claim 1, characterized in that: The surfactant is at least one of nonylphenol polyoxyethylene ether (NP), alkyl polyglycoside (APG), polyether surfactant, stearic acid, fluorocarbon surfactant, and polyvinyl alcohol surfactant.

5. The method for preparing the full-dimensional super-amphiphobic concrete according to claim 1, characterized in that: The hydrophobic modifier is alkylsiloxane, chlorosilane or fluorosilane.

6. The method for preparing the full-dimensional super-amphiphobic concrete according to claim 1, characterized in that: The dispersant is at least one of sodium polyacrylate, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, trisodium phosphate, alkyl aryl sulfonate, polycarboxylic acid dispersant, polyethylene glycol or alkyl benzene sulfonate.

7. The full-dimensional super-amphiphobic concrete prepared by the preparation method according to any one of claims 1 to 6.

8. The use of the full-dimensional super-amphiphobic concrete according to claim 7, characterized in that: The full-dimensional super-amphiphobic concrete is evenly coated on the surface of the substrate by spraying, rolling or brushing, and after it is naturally dried at room temperature, a concrete coating with full-dimensional super-amphiphobic properties is formed; alternatively, the full-dimensional super-amphiphobic concrete slurry is directly poured into a mold, and after it is naturally cured at room temperature, a concrete test block with full-dimensional super-amphiphobic properties is obtained.